Integrating Islamic Psychology into Kiai’s Transformational Leadership: A Model for Teacher Performance Development - Muhimmatul Hasanah; Ahmad Fauzi (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to describe and analyze the transformational leadership model of Kiai based on Islamic psychology in enhancing teachers’ performance at Sunan Drajat Islamic Boarding School. The leadership of Kiai has unique characteristics that emphasize not only administrative aspects but also spiritual, moral, and psychological dimensions. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving Kiai, teachers, and school administrators. Data analysis was conducted using data reduction, display, and conclusion drawing techniques. The findings reveal that the transformational leadership model of Kiai in Sunan Drajat Islamic Boarding School is manifested through four key dimensions: exemplary character (idealized influence), spiritual motivation (inspirational motivation), Islamic value-based intellectual stimulation, and individualized consideration grounded in akhlaq (moral conduct). The integration of Islamic psychological values such as sincerity (ikhlas), patience (sabr), trustworthiness (amanah), and reliance on God (tawakkul) forms the emotional bond between Kiai and teachers. This model effectively enhances teachers’ performance by improving intrinsic motivation, loyalty, and psychological well-being. The study recommends the implementation of Islamic psychology-based leadership training for educational leaders in Islamic institutions.